Physical Activity of Secondary School Adolescents at Risk of Depressive Symptoms - Frömel, Karel; Jakubec, Lukáš; Groffik, Dorota; ChmelÍk, František; Svozil, Zbyněk; Šafář, Michal (The Journal of school health, 2020)
BACKGROUND: The aim of the study is to analyze the associations between depressive symptoms (DS), well-being and different types of physical activity (PA) in adolescents. METHODS: Overall, 368 girls and 228 boys aged 15-19 years were involved in the research. To explore the composition of weekly PA, we used the IPAQ-Long questionnaire, and a pedometer was used to monitor weekly PA. The prevalence of DS was diagnosed by the Bern Subjective Well-Being Questionnaire and the WHO-5 Well-Being Index. RESULTS: The girls and boys who reported the most DS and the lowest level of well-being had significantly less weekly recreational PA. The girls who reported the fewest DS had a 2.12 times greater odds of meeting the 11,000 steps/day recommendation than did the girls with the most DS, whereas we did not detect statistically significant differences in rates of meeting the recommendation in the boys with distinct levels of DS. CONCLUSIONS: The study confirms the stronger negative associations between DS and PA, especially among girls. The greatest opportunities for behavioral change in adolescents at the highest risk of DS are in the promotion of recreational PA.
Keywords: Surveys and Questionnaires; IPAQ; Humans; aktigrafie; Schools; Actigraphy; Female; mladý dospělý; lidé; recommendations; průzkumy a dotazníky; ženské pohlaví; Male; školy; Adolescent; Young Adult; quality of life; Depression; Exercise; pedometer; mužské pohlaví; cvičení; deprese; mladiství; well-being